Faktor Pendukung Dan Faktor Penghambat Pembelajaran Daring Sekolah Dasar Berbasis Whatsapp di Kelas III - Mohammad Masum (Jurnal Pendidikan Tuntas, 2023)
The background of this research is the curiosity of researchers about the Supporting Factors and Inhibiting Factors of Whatsapp-Based Online Learning in Theme 2 Class III SDN 009 Sungai Pagar, Kampar Kiri Hilir District, Kampar Regency, and how to provide solutions to the obstacles that arise in online learning. Online learning can be defined as an effort to connect students with learning resources that are physically separate or even far apart but can communicate, interact or collaborate directly and indirectly with each other. This research is a descriptive research using a qualitative approach to field research. The sampling technique used in this research is purposive sampling and snowball sampling while the data collection tools used are observation, interviews and documentation. The research results obtained in the form of whatsapp-based online learning support factors are; The internet/whatsapp can load and send various learning materials such as explanatory videos, picture messages, and voice messages, can communicate and give learning instructions at any time, students can follow learning from anywhere without having to go to school. The inhibiting factors for whatsapp-based online learning are; quota or data package that runs out quickly, signal is not good, also doesn't have an android cellphone. Based on the conclusions above, the researcher submits some suggestions as follows: For class III teachers at SDN 009 Sungai Pagar to reduce the assignments given to students so that assignments do not pile up or continue to give assignments but in small quantities, while students who do not or do not understand the teacher can make visits to students' homes either individually or in groups, For parents of students to be involved in supervising students during online learning because this plays an important role in the success of online learning, For schools to prepare teams of teachers who are on standby at school to help students who have difficulty in learning